Putting Electricity Where The Rubber Meets the Road [NEWS]. - Jones, W.D.
In-wheel motors can improve fuel economy and safety for hybrid electric vehicles. A motor housed inside a wheel hub can shunt up to 96 percent of the torque it generates directly to the patch of tire that touches the road. With a conventional drivetrain, roughly 20 percent of the power generated by the motor is lost to friction.
Keywords: Electric drive motors; Electric motors; Fuel economy; Hybrid electric vehicles; In-wheel motor; Safety; Torque; Wheel-hub-motor direct- drive systems